Dakwah sebagai Strategi Penguatan Karakter Wirausaha: Analisis Konten dan Peran Komunikasi Religius di BLK Bulukumba - A. Muh Fadil Insana Jafar; Kamaluddin Tajibu; St. Nasriah (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This research aims to describe the ethical role of da’wah messages in building labor independence at the Bulukumba Regency Job Training Center (BLK). With a qualitative and da’wah communication approach, this research collects data from primary and secondary sources through interviews, observation, and documentation. The results showed that the da’wah messages delivered, such as aqidah (sincerity), sharia (charity), muamalah (responsibility), and morals (honesty), were not only related to the provision of material but also formed the character and moral values of the trainees. This research implies the importance of integrating religious values in training programs to form a workforce that is technically skilled and has high moral integrity, highlighting the ethical responsibility of educators and practitioners in the field